Heterosis in Genomic Era: Advances in the Molecular Understanding and Techniques for Rapid Exploitation. (4th May 2021) - Das, Abhijit Kumar; Choudhary, Mukesh; Kumar, Pardeep; Karjagi, Chikkappa G; KR, Yathish; Kumar, Ramesh; Singh, Alla; Kumar, Santosh; Rakshit, Sujay
Abstract: Heterosis has been widely exploited in plants and animals, and also revolutionized agriculture by improving important agronomic traits. However, the molecular mechanism is still remaining elusive. Though different classical models, viz ., dominance, overdominance and epistasis still holds true, the recent studies on epigenomics, transcriptomic, proteomic, metabolomics and circadian model have provided new insights. Multigene models have been proposed as the basis of complementation of allelic and gene expression variation, which is a major probable contributor to heterosis. The evolving epigenetic and genomic field put forward the role of interaction of alleles from different parental genomes in reprogramming the genes involved in stress tolerance, fitness and growth of hybrids. In the majority of the studies, transcriptomic, proteomic and metabolomic studies have found many complex regulatory network changes in genetic, epigenetic, regulatory and biochemical levels and only a few patterns could be established. Thus, heterosis is the outcome of the series of interactions in the genomes. Furthermore, epigenetic modifications of the circadian clock genes and their reciprocal regulators were reported to regulate the expression of downstream genes and pathways leading to more product accumulation in hybrids. Moreover, the majority of the epigenetic studies are limited to Arabidopsis thaliana and Zea mays, however, such studies on different crops may further bring more insights on the role of epigenetic mechanisms in determining heterosis. Further, none of the models is capable to explain heterosis alone which reflects the limitations of the individual model. The present review critically assesses different theories from different fields and also unravels the existing rapid methods to exploit them.